TRANSFORMASI POLA KERJA MASYARAKAT JAWA PADA MASA CULTUURSTELSEL TAHUN 1830-1870 - Kristina Ayu Agustin; Hervina Nurullita; Miskawi Miskawi (Prabayaksa: Journal of History Education, 2026)
The implementation of the Cultuurstelsel (Cultivation System) in Java between 1830 and 1870 represented a major colonial policy introduced by the Dutch government to overcome financial crises following prolonged wars and economic difficulties. Beyond its economic function, the system served as an instrument of colonial control that transformed the socio-economic structure of Javanese society. This study aims to examine how the Cultuurstelsel reshaped the work patterns of Javanese society during 1830–1870. The research employs the historical method, consisting of heuristics, source criticism, interpretation, and historiography, using colonial archives, administrative reports, and nineteenth-century publications as primary sources. The findings indicate that the Cultuurstelsel altered the subsistence-oriented work patterns of Javanese society into a labor system centered on colonial export production. Obligations to cultivate export crops and provide forced labor reduced the allocation of land and labor for food production, contributing to declining agricultural output, poverty, famine, and growing social inequality. The policy also reinforced colonial control over land and labor while creating new forms of social stratification through the involvement of indigenous elites. Although the system introduced infrastructure development and monetary economic practices, its adverse effects outweighed these benefits. In conclusion, the Cultuurstelsel functioned not merely as an economic policy but as an exploitative colonial mechanism that fundamentally transformed the relationship between Javanese society, land, and labor, leaving long-lasting socio-economic consequences.